2020
DOI: 10.1080/14427591.2020.1818611
|View full text |Cite
|
Sign up to set email alerts
|

Adult children’s experiences of family occupations following ageing parents’ functional decline

Abstract: Background. Adult children often live separately from their ageing parents; however, family occupations between them may still be an important aspect of daily life. Previous research showed that, when ageing parents experience functional decline, their adult children's everyday life is affected. Purpose. We aimed to provide insight into adult children's experiences of family occupations when their older parents' exhibit functional decline. Method. This study used a qualitative research design with a constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Metaphors are used as a way of structuring understanding of experiences, 28 therefore can be utilised as a method of expanding understanding through linking familiar experiences to those less familiar or more complex. Recent examples in qualitative health research include a road trip in families with a Down Syndrome child, 29 welfare systems as a pinball machine 30 and an iceberg representing caring for ageing parents 31 . In these examples and the current study, the authors selected a metaphor during the analytic process with the aim of improved understanding of complex topics reported in the findings 28 and described with the use of symbols from the real world 6 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaphors are used as a way of structuring understanding of experiences, 28 therefore can be utilised as a method of expanding understanding through linking familiar experiences to those less familiar or more complex. Recent examples in qualitative health research include a road trip in families with a Down Syndrome child, 29 welfare systems as a pinball machine 30 and an iceberg representing caring for ageing parents 31 . In these examples and the current study, the authors selected a metaphor during the analytic process with the aim of improved understanding of complex topics reported in the findings 28 and described with the use of symbols from the real world 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Recent examples in qualitative health research include a road trip in families with a Down Syndrome child, 29 welfare systems as a pinball machine 30 and an iceberg representing caring for ageing parents. 31 In these examples and the current study, the authors selected a metaphor during the analytic process with the aim of improved understanding of complex topics reported in the findings 28 and described with the use of symbols from the real world. 6 This metaphor was selected through a collaborative process where lay responders were provided with multiple metaphor options in combination with the analytic themes to select the metaphor of best fit.…”
Section: Methodsmentioning
confidence: 99%
“…11 A more recent study found that adult children carers considered themselves to play an important role supporting elderly parents in need of care. 14 Since 2011, community health care services have been encouraged to integrate digital assistive technology in the home care services to increase quality and efficiency in the health services and to reduce costs. 15 This is in line with international policy and research.…”
Section: Introductionmentioning
confidence: 99%